2001
DOI: 10.2307/3078896
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Response to Artificial Selection for Light Sensitivity in Guppies (Poecilia reticulata)

Abstract: We performed artificial selection on the visual system in guppies (Poecilia reticulata), using the optomotor reaction threshold as the selection criterion. Two lines were selected for increased sensitivity to blue light, two were selected for increased sensitivity to red light, and two were unselected controls. There was significant response to selection in all four selected lines and significant heritability for sensitivity. An examination of the spectral sensitivity function showed that the form of the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…Nevertheless, several studies suggested a causal relationship between visual perception and mating decisions at the level of species divergence [36], [52], [53]. We thus propose that variation in visual sensitivity in females might contribute to mating preferences since an improved visual perception should promote detection of male red coloration as well as discrimination between varying degrees of male coloration.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Nevertheless, several studies suggested a causal relationship between visual perception and mating decisions at the level of species divergence [36], [52], [53]. We thus propose that variation in visual sensitivity in females might contribute to mating preferences since an improved visual perception should promote detection of male red coloration as well as discrimination between varying degrees of male coloration.…”
Section: Introductionmentioning
confidence: 83%
“…Alternatively, among-individual variability in genetic predispositions can simply be expressed in phenotypic differences in the sensory apparatus which may, for example, result in different perceptual and discriminatory abilities in females [21]. However, the proximate basis of variation in female preference functions is rarely explored [36], [37] although, as previously depicted, reliable knowledge of the underlying mechanisms should provide useful information on the evolution of sexually selected traits. For instance, the sensory drive hypothesis addresses the mechanistic basis of mating preferences in that it predicts that females prefer a specific male signal design which maximally stimulates their sensory system and is thus more conspicuous and easier to detect in their local environment [38][40].…”
Section: Introductionmentioning
confidence: 99%
“…Artificial selection experiments are invaluable tools for directly investigating the response to selection, general evolvability (sustainability of the response) and the existence of genetic correlations [16], [17]. Few studies have applied these methods to teleosts models of evolutionary and not aquacultural research [18], [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…Endler et al [61] showed that light sensitivity changed in response to artificial selection in guppies. Recent studies on cone visual pigments of Lake Malawi cichlids [21] and zebra fish [62] indicated that the relative expression levels of different opsin genes reflect spectral sensitivity of the fish.…”
Section: Discussionmentioning
confidence: 99%